School Literacy Movement By Cultivating The Character Of Like Reading Through Procurement Of Story Books At Sb Wira Damai, Selangor, Malaysia - Lasmiatun, Lasmiatun; Istifaroh, Siti (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAI Al-Khiarat Pamekasan, 2024)
Implementation of school literacy conducted at SB Wira Damai in Selangor, Malaysia, aimed to increase the love of reading among students by providing story books. The program was designed to increase students’ interest in reading and participation in the learning process by focusing on providing a variety of books that are appropriate to the students’ age and interests. During the 28-day observation period, the study showed a significant increase in students’ participation in literacy activities, reflecting greater participation in literacy practices. Activities such as book reviews and storytelling competitions were designed to create a fun and interactive atmosphere. Periodic evaluations were conducted to measure the effectiveness of the program and provide recommendations to other schools. The results of this study indicate that school literacy training can positively influence students’ interest in reading and contribute to their cognitive and academic development. Thus, a reading culture grows and develops among students, aiming to make them more knowledgeable and competitive human beings.